Mulheres e Megaprojetos em Barra do Riacho — Aracruz (ES) - Aguilar, Daniela Batista (2021)
This research starts from a socio-anthropological concerning the gender issue in a context of large development projects, from the perspective of women who live and work in a location directly affected by the multiple effects of these projects, in Barra do Riacho (BR), a neighborhood in the municipality of Aracruz in the state of Espírito Santo. I am interested in understanding how these women assimilate this reality, act and/or suffer the developmentalist repercussions in the figure of mega-enterprises, a context of inflamed risk, invisibility and socio-environmental vulnerability, since the routine activities of work and social recognition are markedly of exploitation and degradation, with a unique impact on the lives of women in the locality. The theoretical framework discusses the hegemonic capitalist economic system and, in a collateral way, raises the criticism of the Eurocentric scientific institution, as well as the predominantly masculine academic establishments. All these reflections revolve around the question of power in patriarchal society and its forms of affectation, especially for women and ecosystems. Through the methodology of life history, the trajectories of two women with different experiences, professional occupations and worldviews are unveiled, providing the analysis of their dynamics of existence, sociability and resistance in such a context, reconciling, theoretically, with the voices of other women who research such realities and scenarios from a feminist and ecofeminist perspective. The life story, the basic axis of this work, proposes to assemble the image of a large mosaic, built from the place where these women live and work, with their respective faces or layers of complex and multiple affectations.